Pembuatan Sabun Cair Cuci Piring untuk Pengembangan Wirausaha Karang Taruna di Pondok Ungu Permai Sektor V, Babelan, Bekasi Utara - Turseno, Andi; Rosihan, Rifda Ilahy; Nugroho, Oki Widhi; Aji, Sonny Nugroho; Sumanto (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2024)
The need for liquid dish soap is increasing because some people have started to switch from using cream soap for washing dishes. In addition, the use of liquid dish soap is easier and more effective in cleaning stains on kitchen utensils. The basic ingredient of liquid dish soap is a surfactant chemical compound which has a function as a stain remover on kitchen utensils. The purpose of this community service is to provide knowledge to youth organizations in terms of making liquid soap to develop youth entrepreneurs at Ponduk Ungu Permai Sector V, Babelan, North Bekasi. The method used in this community service activity is discussion, presentation, knowledge sharing, and the practice of making dish soap. The result of this community service is in the form of a finished product of liquid dish soap according to the method provided.